The Locus Coeruleus- Norepinephrine System in Stress and Arousal: Unraveling Historical, Current, and Future Perspectives - Ross, Jennifer A.; Van Bockstaele, Elisabeth J. (Frontiers in Psychiatry, 2021)
Arousal may be understood on a spectrum, with excessive sleepiness, cognitive dysfunction, and inattention on one side, and hypervigilance, panic, and psychosis on the other side of being in a wakeful state. However, historically, the concepts of arousal and stress have been difficult to define as measurable experimental variables. Divergent efforts to study these subjects have given rise to several disciplines, including neurobiology, neuroendocrinology, and cognitive neuroscience. We discuss technological advancements that chronologically led to our current understanding of the arousal system, with a focus on the multifaceted nucleus locus-coeruleus. We share our current perspective as well as the hypotheses of others in the context of our current technological capabilities and future developments that will be required to move forward in this area of research.